Prevalence of sarcopenia among community‐dwelling elderly of a medium‐sized South American city: results of the COMO VAI? study. Issue 2 (9th June 2015) - Barbosa‐Silva, Thiago G.; Bielemann, Renata M.; Gonzalez, Maria Cristina; Menezes, Ana Maria B.
Abstract: Background: There is insufficient data concerning sarcopenia prevalence in South America. The aim of this study was to estimate sarcopenia prevalence and its clinical subgroups in a Southern Brazilian city. Methods: A cross‐sectional population‐based study was performed among community‐dwelling elderly aged 60 years or over. Subjects were evaluated according to the European Working Group on Sarcopenia in Older People established criteria. Muscle mass was estimated by calf circumference (CC). Cut‐off CC points were defined by a subsample's dual X‐ray absorptiometry estimation of the appendicular skeletal muscle mass index (ASMI), which was subsequently compared with the values of a young adult population from the same city. Muscle strength was measured by manual dynamometry. Muscle performance was assessed through the 4 m gait speed test. Results: The three diagnostic tests were performed in 1291 subjects. CC of ≤34 cm (males) and ≤33 cm (females) were defined as indicatives of low ASMI. The overall sarcopenia prevalence was 13.9% (CI95% 12.0; 15.8%). Its frequency was significantly higher among elderly with low schooling, without a partner, with low socioeconomic status, smokers, inactive, and with low body mass index. A higher prevalence of pre‐sarcopenia was found in the youngest elderly; a higher prevalence of the clinical stages of the syndrome was found in older age groups. Conclusions: Approximately one in ten elderly aged 60–69 years was in the preclinical stage of the disease. This is the age group in which public policies should focus to establish early diagnosis and prevent clinical progression of the syndrome.